Nilai Nilai Akhlaqul Karimah Dalam Surah Al Fatihah - Akhrie Ramadayanto; Dadang Darmawan; Wildan Taufiq (UIN Sunan Gunung Djati Bandung, 2021)
Surah Al-Fatihah is called Al Fatihah because the Qur'an begins with this surah. In addition, it is also called the Ummul Kitab because Al Fatihah contains all the problems contained in the Qur'an, namely divinity, nature, the afterlife, worship, and history. Al-Qur'an surah Al Fatihah also has moral values that can reference Indonesia's young generation experiencing a moral crisis. Moral education is essential for the next generation of the nation. It is not enough for a person to be given knowledge alone and the provision of morals that become the capital for a person to live a successful life in the future. The author used the tahlili interpretation method, which is a method that intends to explain the content of the verses of the Qur'an from all its aspects, from the Book of Tafsir Al-Maraghi and Tafsir Al-Misbah. Therefore, this method is very appropriate to reveal the content of the values of a good deed in the Surah al-Fatihah. This research is a literature study using the comparative form of Al Misbah's interpretation and Al-Maraghi's interpretation. Both have the same style in interpreting the verse, namely adabul ijtima'i, namely social society. The results showed that the moral values contained in the Surah Al Fatihah in the first verse Bismillahirrahmanirrahim, that Muslims must read at every start of any word or deed.